2013
DOI: 10.1002/admi.201300027
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric Order Control of the Dirac‐Semimetal Phase in GeTe‐Sb2Te3 Superlattices

Abstract: The quasibinary GeTe-Sb 2 Te 3 system (primarily the Ge 2 Sb 2 Te 5 composition, or GST225) has been long used in optical memory devices such as re-writable DVD-RAM and are also a leading candidate for the nonvolatile electronic memory known as phase-change random-access memory (PC-RAM); last year Samsung and Micron have started shipping these devices into the market. The basis of the phase-change storage is a large property contrast between the crystalline and amorphous phases; the idea dates back to the 1960… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
184
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(196 citation statements)
references
References 34 publications
7
184
3
Order By: Relevance
“…In that connection, chalcogenide superlattices (CSL) [123,124] and nanocrystals [125,126] were investigated for their capabilities to serve in such systems. In particular, interfacial phase-change materials (iPCMs) [127][128][129], in which the transformations do not occur between an amorphous and a crystalline phase, but between two crystalline phases, are of great interest as candidate systems. The more recent determinations of the crystal structure for the ternary Ge 4 Se 3 Te [31] (Figure 7) indicated that the type of structure observed for that chalcogenide may serve as an archetype for future PCMs.…”
Section: The Role Of Vacancies and Structural Preferences In Phase-chmentioning
confidence: 99%
“…In that connection, chalcogenide superlattices (CSL) [123,124] and nanocrystals [125,126] were investigated for their capabilities to serve in such systems. In particular, interfacial phase-change materials (iPCMs) [127][128][129], in which the transformations do not occur between an amorphous and a crystalline phase, but between two crystalline phases, are of great interest as candidate systems. The more recent determinations of the crystal structure for the ternary Ge 4 Se 3 Te [31] (Figure 7) indicated that the type of structure observed for that chalcogenide may serve as an archetype for future PCMs.…”
Section: The Role Of Vacancies and Structural Preferences In Phase-chmentioning
confidence: 99%
“…Introduction-Recently, Dirac and Weyl semimetals, which host bulk gapless excitations obeying quasirelativistic fermion equations, have attracted much attention in condensed matter physics [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Dirac semimetals have been theoretically predicted [1][2][3] and experimentally demonstrated in (Bi 1−x In x ) 2 Se 3 [4,5], Na 3 Bi [6,7] and Cd 3 As 2 [8,9].…”
mentioning
confidence: 99%
“…11 Furthermore, several superlattice structures including GeTe/Sb 2 Te 3 have been theoretically predicted to exhibit unusual properties forming topological insulators or Dirac semimetals, leading to the experimental confirmation of unusual magnetic properties despite the lack of magnetic elements. [12][13][14][15] The most widely used techniques to fabricate 2D chalcogenides are exfoliation from a bulk single crystal, chemical vapor deposition (CVD), and molecular beam epitaxy (MBE). [16][17][18][19][20][21] However, the area of films that can be fabricated by exfoliation is limited and sample sizes are not uniform.…”
mentioning
confidence: 99%